Using guerrilla marketing in the Republic of Kazakhstan (Вестник КазНУ. Серия Экономическая, 2016)
Effective communication policy of any company ensures its successful work and survive in a competitive environment. There is a need to search for and application of innovative technologies to promote products and services to meet the requirements of today. Currently, the use of low-bud get necessary communication technologies, but at the same time having a high efficiency in the overall progress. In this regard, this article discusses the importance of the use of guerrilla marketing as one of the promotion of new technologies, and the history of its development is shown in inter national practice, the main instruments of influence. Also, the necessity of the use of guerrilla marketing to domestic realities of the market. The analysis of the development of the sphere of cellular communication in the Republic of Kazakhstan, is widely used at the present time various tools of guerrilla marketing.